RENEWABLE EFFECTS OF THE CULTURE SELFIE MODEL IN THE PERSPECTIVE OF GLOBAL TOURISM DEVELOPMENT - Isdarmanto, Isdarmanto; Riantiarno, Agung; Maftucha, Maftucha (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2019)
Selfie photo activity has a close effect on the development of one's life in creating selfconfidence and acculturation from the development of self-actualization which is the highest level of Abraham Maslow's Need theory. Selfie and social media in arts as form of existence are the right word to response upon the development of society. There is an issue would be discuss in this article; discuss about elements of arts existence, commodification of arts, and patterns of consumption. By using qualitative research methods to obtain effective research results in accordance with case studies of the development of the world of selfie tourism that cannot be controlled in line with the development of multimedia and the gadget era that is able to accelerate various information needs in the world of social communication media. The purpose of this research is to open an understanding that the development of the life of the general public can develop towards a positive direction.Keywords: Selfie photos. Self-image, world Selfie tourism